Transmitarrays for Wireless Power Transfer on Earth and in Space - Jesse Brunet; Alex Ayling; Ali Hajimiri (IEEE Journal of Microwaves)
We present a space solar power system using transmitarrays for lowering the system's LCOE (Levelized Cost of Energy). We discuss the theoretical framework for transmitarrays in the context of wireless power transfer, including the transmission phase limit associated with layered frequency selective surfaces. We then present a proposal for using transmitarrays to lower the LCOE of space solar powered systems that are limited by the transmitting aperture size. Finally, we design and fabricate a low-cost, lightweight static transmitarray prototype and demonstrate a $\sim$ 2.4x increase in power transferred from the phased array transmitter to the rectenna receiver.